EVALUASI PERILAKU HARIAN LUTUNG JAWA (Trachypithecus auratus E. Geoffroy Saint-Hilaire 1812) PASCA PELEPASLIARAN DI GUNUNG BIRU BATU JAWA TIMUR - Sukmayanti, Rifka Hardina; Aryanti, Nirmala Ayu; Syarifuddin, Amir; Kurniawan, Iwan (Jurnal Belantara, 2024)
The Mount Biru protect forest is still maintained the biodiversity so that it is able to support a variety of animals in it, one of which is a habitat for the release of the javan langurs group (T. auratus). This study aims to determine the daily behavior of the javan langur after rehabilitation and release to evaluate the development of population behavior and barriers in the same group since 2014. The study used a focal animal sampling method combined with scan sampling to observe daily behavior (eating, social, resting, and moving) one female javan langur released in 2014. It was observed that post-release individuals had higher resting activities (38.91%) and the lowest allo-grooming social activities (5.08%). The results of the different test calculations using Chi Square can be concluded that there are significant differences in the daily behavior of the Javan langur after release in 2015, 2019 and 2021.